A review of different techniques utilized for-casting crop yield - Bhardwaj, Priya; Singh, Mrityunjay (International Journal of Engineering and Technology, 2018)
The farming structures the establishment of Indian economy. The harvest creation mainly depends on atmospheric conditions such as climate change, rain, soil etc., that impacts on yield improvement. The most of existing algorithms for crop yield prediction utilizes the existing data mining (DM) techniques for forecasting. This paper exhibits an overview on some of the existing techniques mostly used for crop yield prediction.